Intensification of microbial exopolysaccharide ethapolan biosynthesis on mixture of molasses and sunflower oil - Pirog, Tatiana; Voronenko, Andryi; Ivahniuk, Mykola (My University, 2017)
The purpose of the research was to establish Acinetobacter sp. IMV B-7005 cultivation conditions, which provide the maximal synthesis of microbial exopolysaccharide ethapolan on a mixture of molasses and sunflower oil, and to explore the possibility of replacing refined oil in a mixture with molasses for waste one. On the basis of theoretical calculations of energy consumption for the synthesis of ethapolan and biomass, it was determined that the optimal molar ratio of the concentrations of energy-deficient (sucrose) and energy-excessive (sunflower oil) substrates in the mixture was 1.0:0.9. Experiments have shown that the highest values of exopolysaccharide synthesis were observed at the molar ratio of monosubstrates in mixture 1.0:1.1, which is as close as possible to the theoretically calculated one. It was shown that increasing concentration of molasses and refined oil in mixture from 1.0 to 1.5% was accompanied by increase in amount of synthesized exopolysaccharide and its synthesizing capacity in 1.2 and 1.3 times, respectively. The possibility of replacing refined oil in a mixture with molasses for various types of waste (after frying potatoes, meat, vegetables and mixed) was established. The maximum parameters of exopolysaccharide synthesis (concentration 14 g/l, synthesizing capacity 3.5 g exopolysaccharide /g biomass) were observed when using mixed waste oil for both inoculum obtaining and EPS biosynthesis. The obtained results testify to the possibility of development of universal technology for obtaining microbal exopolysaccharide ethapolan on a mixture of waste (molasses and waste oil) independent of the type and provider of waste oil. Метою роботи було встановити умови культивування Acinetobacter sp. ІМВ В-7005, які забезпечували би максимальні показники синтезу мікробного екзополісахариду етаполану на суміші меляси та соняшникової олії, а також дослідити можливість заміни рафінованої олії в суміші з мелясою на відпрацьовану. На основі теоретичних розрахунків енерговитрат на синтез етаполану та біомаси визначено, що оптимальне молярне співвідношення концентрацій енергетично дефіцитного (сахароза) та надлишкового (соняшникова олія) субстратів у суміші становить 1,0:0,9. Експерименти показали, що найвищі показники синтезу екзополісахариду етаполану спостерігалися за молярного співвідношення моносубстратів у суміші 1,0:1,1, максимально наближеного до теоретично розрахованого. Підвищення концентрації меляси та рафінованої олії у суміші з 1,0 до 1,5% супроводжувалося збільшенням кількості синтезованого екзополісахариду етаполану та його синтезувальної здатності в 1,2 і 1,3 раза відповідно. Встановлено можливість заміни рафінованої олії в суміші з мелясою на різні типи відпрацьованої (після смаження картоплі, м’яса, овочів та змішану). Найвищі показники синтезу екзо- полісахариду етаполану (концентрація 14 г/л, синтезувальна здатність 3,5 г екзополісахариду етаполану/г біомаси) спостерігалися за умови використання змішаної відпрацьованої олії як для одержання посівного матеріалу, так і біосинтезу екзополісахариду етаполану. Одержані результати засвідчують можливість створення універсальної технології одержання мікробного екзополісахариду етаполану на суміші відходів (меляси та відпрацьованої олії), незалежно від типу та постачальника відпрацьованої олії.
Keywords: кафедра біотехнології і мікробіології; мікробні екзополісахариди; інтенсифікація синтезу; суміш субстратів; microbial exopolysaccharides; synthesis intensification; mixture of substrates